5‐HTTLPR and anxiety modulate brain‐heart covariation. (27th February 2013) - Mueller, Erik M.; Stemmler, Gerhard; Hennig, Jürgen; Wacker, Jan
Abstract: To date, little is known about genes affecting the interplay of brain and heart activity. Because serotonin (5‐HT) is involved in corticovagal neurotransmission, we tested whether the 5‐HT transporter polymorphism 5‐HTTLPR affects brain‐heart covariation. Further, associations with neuroticism/anxiety (NANX) were tested, as anxiety is related to 5‐HT and neurogenic changes of heart period (HP). N  = 168 participants performed a time‐estimation task while EEG and HP were recorded. Brain‐heart covariation was measured using time‐lagged within‐subject correlations of centromedial feedback‐evoked single‐trial EEG at 300 ms and subsequent changes of HP. EEG‐HP correlations were higher in 5‐HTTLPR long allele carriers. Moreover, after negative feedback, EEG‐HP correlations and feedback‐related negativity amplitudes independently correlated with NANX. The results indicate that individual differences in brain‐heart covariation relate to 5‐HT and NANX.